Risks and risk management in family takaful - Mohd. Zain, Nor Razinah; Bhatti, Farhad Ahmed; Salman, Syed Ahmed (International Association of Islamic Banks Karachi, Pakistan, 2022)
Takaful is a financial planning tool that can be used as an alternative to conventional insurance. Generally, takaful products are divided into general Takaful and family takaful. A feature of the General Takaful is that it has a short-term policy and its liability coverage is limited to material losses only. On the other hand, family takaful is a long-term policy that includes savings and an investing component. Although the tabarru fund protects them, the participants can also benefit from the investment returns and savings generated by Shariah-compliant assets. The primary objective of this article is to identify the many types of risks that Family Takaful operators in Malaysia are exposed to and their methods of dealing with and managing these risks. This article is based on a method of library research. In addition, the article highlights the difficulties faced by Family Takaful operators in Malaysia. The hazards associated with running a family takaful business are usually related to operations and investment. Non-compliance risks with Shariah laws, underwriting risks, human resource risks, and fiduciary risks are all risks that exist on the operational side of the business. These risks might occur at any point during the business process. The takaful operator may encounter market, credit, liquidity concerns, and other risks commonly associated with investment on the investment side of the equation. In addition, the researcher offered suggestions on how to mitigate these dangers.